Structural equation models for finite mixtures: Simulation results and empirical applications - Dirk Temme; John R. Williams; Lutz Hildebrandt (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
Unobserved heterogeneity is a serious but often neglected problem in structural equation modelling (SEM) challenging the validity of many empirical results. Recently, a finite mixture approach to SEM has been proposed to resolve this problem but until now only a few studies analyse the performance of the relevant software. The contribution of this paper is twofold: First, results from a Monte Carlo study into the properties of the program system MECOSA are presented. Second, an empirical application to data from a large-scale consumer survey in the fast moving consumer goods industry is described.
urn:nbn:de:kobv:11-10048911
Keywords: 330; Monte Carlo simulation; Structural equation modelling; Unobserved heterogeneity; Model-based clustering; Finite mixtures